Perancangan Multimedia Interaktif Sebagai Media Promosi Rental Mobil QRC: Designing Interactive Multimedia as a QRC Car Rental Promotion Media - Samad Samad; Harri Sakti Mulia Nasution (YCMM, 2021)
The development of various technologies and in connection with the running depth of this globalization era can really help and make it easier for humans to carry out and carry out various activities, such as for example to see the prices of cars that are rented in general. Therefore, it can be seen that with this technology and design it will can make it easier for us to do everything, and as a general idea is we think about a habit or an activity that is often done and done by humans, and we define car rental as a habit that is mostly done for business owners. As one of the businesses engaged in Car Rental, which operates in Aviari Sawang Permai, it serves a variety of car rental needs, both for companies and individuals, for long and short term.